Islamic Cultural History Learning With Picture and Picture Model - Azzahra, Mega; Sriwardona, Sriwardona; Yani, Resi Anda (STIT Ahlussunnah Bukittinggi, 2025)
The purpose of this study was to describe how the application of the Picture and Picture learning model can help improve students' learning outcomes in the Islamic Cultural History (SKI) lesson. The Picture and Picture model is an approach in cooperative learning that uses pictures as a medium to invite students to interact in the learning process. This study was conducted using the classroom action research (CAR) method in two cycles. The subjects of this study were grade VII students at one of the Madrasah Tsanawiyah. The data collection tools used were observation, interviews, and learning capacity tests carried out by students. The first result found in this study was that Picture and Picture can motivate and improve understanding of Islamic history material in an introspective manner. This increase is substantive, namely an increase in expected values, and process, namely, active student involvement during teaching. Therefore, Picture and Picture should be used in teaching SKI because it is varied and not boring.